'Min Al-Mukhayyam' ('From the Camp'): Discourses of Difference and the Boundaries of Exile amongst Palestinian Refugees in Jordan. Issue 1 (1st June 2021) - Pérez, Michael
Abstract: This article examines the implications of long-term encampment and exile for the meaning of Palestinian identity amongst refugees. It shows how the conditions of Palestinian camps in Jordan function as a key marker of social difference between refugees of the camps and the city. Whereas camp refugees see the hardships of camp life as conditions to be confronted, urban refugees take them as constitutive features of a socially distinct refugee. As I argue, the distinctions between camp and city refugees illustrate how the refugee category and the humanitarian camp exceed the ideology and function of humanitarianism. They demonstrate how, in protracted refugee situations, the refugee label and the historical context of the camp can become socially significant and contested features of identity.